اسهامات جاك بيرك في الانثربولوجيا المغاربية - قريصات, الزهرة (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
يعتبر بيرك انثربولوجيامغاربيا من الطراز الأول فدراساته النظرية وتجربته الإدارية والمهنية ومعايشته للمجتمع المغربي والجزائري تجعل منه انثربولوجيا باستحقاق من خلال كتاباته المختلفة التي تأرجحت بين المعرفة والسلطة ،بين النظري والعملي،بين البنية والحدث، بين الفردانية والعالمية .والمتصفح كرونولوجيا لكتابات جاك بيرك يجد أن كتاباته لم تتمحور حول الإسلام فقط بل تجاوزتها إلى عرض معايشته كملاحظ وفاعل في الحياة الاجتماعية وتأثرا واضحا باللغة والدين والعادات والهوية. إن القراءة في "OpéraMinora" تبين بعمق أن جاك بيرك كان انثربولوجيا متميزا ترك تراثا غنيا في دراسة المغرب الكبير مستخدما وسائل البحث الانثربولوجي المختلفة بدقة متناهية، وفي هذه المداخلة سنتناول الإسهام التنويري لجاك بيرك في إبراز الجانب الانثربولوجي في دراسة المغرب العربي وأهم المحطات الأكاديمية والمنهجية. Berk is, anthropologically talking, a typical Maghrebian. His theoretical studies and administrative and professional experience, and his life in the Moroccan and Algerian societies made of him a worthily anthropologist throughout his different books which dealt with knowledge and power, theory and practice, between the structure and the event, between the individualism and the worldwide. The one who browse Berk’s books chronologically finds that they don’t focus only on Islam but extending to living it as both an observer and actor into the social life. He also was influenced with all of the language, the religion, the customs, and the identity of the region.  When reading ‘Opera  Minora’, it would be obvious to notice that Jacques Berk used to be a distinct anthropologist who left a great heritage in the study of the Great Maghreb behind him utilizing the acute and infinite  various anthropological research tools. In this intervention, we will deal the enlightening contribution of Berk in demonstrating the anthropological aspect in studying the Arab Maghreb and the main academic and methodological stations.